Análise fonética e fonológica da língua puruborá. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2005)
The Puruborá language is one of the indigenous languages classified as an isolated language within the Tupi trunk (Rodrigues, 1984/85). This fact is justified by the existence of only two semi-speakers, remnants of the Puruborá people, who, due to a long period without speaking the language, only remember lexical items and a few phrases. The present research subproject aims at developing the acoustic phonetic analysis of the Puruborá language vowels and feeding a lexical database, with a view to the future creation of a Puruborá-Portuguese dictionary. Thus, this work will contribute to refine the phonetic and phonological analysis, already started, of this language (Galucio, forthcoming). This acoustic study consists of measuring the first three formants (F1, F2, F3) of vowels and their respective durations during speech production, using the software programs Signal Explorer and Formant Explorer. Through these measurements, the phonetic quality of each vowel can be identified, mainly through the distribution of F1 and F2 values in the vocal tract, which will be presented in graphical form. The elaboration of the dictionary is a long-term proposal that is being developed as the collected language data is systematized and revised. At this stage of the subproject, the language data is being entered into the Toolbox program for storing data and organizing dictionaries.
Phonetic and phonological analysis of the Purubora language.
Keywords: Puruborá; Língua indígena; Tronco tupi; CNPQ::CIENCIAS HUMANAS